Korelasi Efikasi Diri dan Motivasi Belajar dengan Hasil Belajar Mahasiswa Pendidikan Jasmani - Pambudi, Yudhi Teguh; Widorotama, Angger; Fahri, Achmad Syakura; Farkhan, Mukhammad Miftakhul (Universitas Hamzanwadi, 2022)
The existence of obstacles to learning outcomes in the form of academic achievement, especially Physical Education students, needs to be studied from a psychological perspective to improve learning outcomes. This research is a cross sectional study. The subjects of this study were 53 active students of the Physical Education study program. The research instrument of self-efficacy and learning motivation used a Likert-scale questionnaire based on the self-efficacy dimensions proposed by Bandura and the indicators of learning motivation proposed by Schunk. The questionnaire was validated by psychologists, linguists, and physical education experts, and tested on active students other than subjects for statistical validity and reliability. The results showed that the correlation coefficient for self-efficacy and learning outcomes was 0.558 with a significance level of 0.001. While the value of the correlation coefficient for learning motivation with learning outcomes is 0.709 with a meaning level of 0.001. The simultaneous correlation between self-efficacy and learning motivation with learning outcomes has an R value of 0.753 and an R Square value of 0.566. The conclusion obtained is a positive and significant relationship on self-efficacy with learning outcomes. Positive and significant relationship for learning motivation with learning outcomes. Simultaneously positive and significant relationship for self-efficacy and learning motivation with learning outcomes.